Effects of Adding Active Elements to Aluminum-Based Filler Alloys on the Bonding of 6061 Aluminum Alloy and Alumina - Yu-Kai Sun (MDPI AG, 2021)
In this study, AA6061/AA6061 and AA6061/alumina were directly brazed with Al10.8Si10Cu, Al10Si10Cu4Ti and Al10Si10Cu4Ti0.1RE filler alloys at 530 °C for 10 min without the use of flux. The addition of titanium and rare-earth elements into Al10.8Si10Cu alloy effectively improved the bonding shear strengths of AA6061/AA6061 and AA6061/alumina joints. The highest joint shear strengths were 61.1 and 19.2 MPa, respectively. The Al10.8Si10Cu filler alloy without titanium and rare-earth elements could not wet on the alumina and caused failure of the AA6061/alumina joint. The shear strengths of the AA6061/AA6061 and AA6061/alumina joints both strongly depended on the active element addition. Due to the high chemical activity of the rare-earth elements, they formed AlLa between the Al10Si10Cu4Ti0.1RE filler alloy and alumina. The addition of rare-earth elements into Al10Si10Cu4Ti filler alloy resulted in significant enhancement of the average bond strength of AA6061/alumina joints, from 8.0 to 14.8 MPa.